Associations between the human immune system and gut microbiome with neurodevelopment in the first 5 years of life: A systematic scoping review. Issue 2 (11th January 2023) - Mancini, Vincent O.; Brook, Juliet; Hernandez, Christian; Strickland, Deborah; Christophersen, Claus T.; D'Vaz, Nina; Silva, Desiree; Prescott, Susan; Callaghan, Bridget; Downs, Jenny; Finlay‐Jones, Amy
Abstract: The aim of this review was to map the literature assessing associations between maternal or infant immune or gut microbiome biomarkers and child neurodevelopmental outcomes within the first 5 years of life. We conducted a PRISMA‐ScR compliant review of peer‐reviewed, English‐language journal articles. Studies reporting gut microbiome or immune system biomarkers and child neurodevelopmental outcomes prior to 5 years were eligible. Sixty‐nine of 23, 495 retrieved studies were included. Of these, 18 reported on the maternal immune system, 40 on the infant immune system, and 13 on the infant gut microbiome. No studies examined the maternal microbiome, and only one study examined biomarkers from both the immune system and the gut microbiome. Additionally, only one study included both maternal and infant biomarkers. Neurodevelopmental outcomes were assessed from 6 days to 5 years. Associations between biomarkers and neurodevelopmental outcomes were largely nonsignificant and small in effect size. While the immune system and gut microbiome are thought to have interactive impacts on the developing brain, there remains a paucity of published studies that report biomarkers from both systems and associations with child development outcomes. Heterogeneity of research designs and methodologies may also contribute to inconsistent findings. Future studies should integrate data across biological systems to generate novel insights into the biological underpinnings of early development.